Alberta Stroke Program Early CT Score and collateral status predict target mismatch in large vessel occlusion with delayed time windows - Hang, Yu; Wang, Chen dong; Ni, Heng; Cao, Yuezhou; Zhao, Lin Bo; Liu, Sheng; Shi, Hai-Bin; Jia, Zhenyu (Journal of neurointerventional surgery, 2023)
BackgroundThe Alberta Stroke Program Early CT Score (ASPECTS) and collateral score (CS) are two readily available imaging metrics for the evaluation of acute ischemic stroke (AIS) with large vessel occlusion (LVO).ObjectiveTo investigate the predictive value of the ASPECTS combined with CS in detecting patients with CT perfusion (CTP) target mismatch in delayed time windows.MethodsOne hundred and sixty-four patients with LVO-AIS were included. ASPECTS was assessed on non-contrast CT (NCCT). CS was evaluated on single-phase CT angiography (sCTA). Target mismatch was defined as a CTP core volume ≤70 mL, mismatch ratio ≥1.8, and absolute mismatch volume ≥15 mL. Spearman correlation analysis and receiver operating characteristic curve analyses were performed.ResultsThe median NCCT ASPECTS of the 164 patients was 8 (IQR 6–9), median sCTA-CS was 2 (IQR 1–2), and median CTP core volume was 8 mL (IQR 0–29.5). There was a strong correlation between NCCT ASPECTS and CTP core volume (rs=−0.756, p<0.0001) and a moderate correlation between the sCTA-CS and CTP core volume (rs=−0.450, p<0.0001). Integrating NCCT ASPECTS and sCTA-CS provided a higher area under the curve (AUC) for predicting target mismatch (AUC=0.882; sensitivity, 89.1%; specificity, 77.8%; p<0.001).ConclusionsNCCT ASPECTS had a strong correlation with CTP core volumes in patients with LVO-AIS in delayed time windows. Combining NCCT ASPECTS with sCTA-CS resulted in a more accurate prediction of target mismatch. If a CTP scan is not available, NCCT ASPECTS combined with sCTA-CS may guide clinicians in making treatment decisions.